Sistem Informasi Penyewaan Perlengkapan Pernikahan Di Nellysalon Waingapu Berbasis Web - Sri Rani; Arini Aha Pekuwali; Trisari Dewi Novyanti Bertha Mira (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The development of technology as a medium for delivering information has provided great benefits for business owners, including in the field of wedding equipment rental. However, Nellysalon Waingapu in Waingapu faces several problems, such as a lack of complete information in promotional media and manual rental records. To overcome this problem, the development of a web-based Wedding Equipment Rental Information System is proposed. This system allows customers to get detailed information about rental packages, prices and status of rented items. Apart from that, this system also helps business owners in storing and processing rental data quickly and accurately. The development method used is the waterfall model from SDLC. Test results show that this system is well received by users, with an average score of 70.6 in the SUS test. Thus, the Wedding Equipment Rental System at Nellysalon Waingapu is suitable for use by system users..